Real and illusory reports of posttraumatic growth and their correlation with well-being: an empirical examination with special focus on defence mechanisms - Börner, Michaela (2016)
Reports of posttraumatic growth can sometimes be illusory. Several researchers have argued that reports of posttraumatic growth may incorporate two separate phenomena, namely real posttraumatic growth and illusory posttraumatic growth. However, it is not often made explicit which kinds of illusions indicate illusory posttraumatic growth. An explicit conceptualisation of illusory posttraumatic growth is, however, necessary in order to investigate the research questions within this thesis, namely (a) whether reports of posttraumatic growth are correlated with illusions and (b) whether real posttraumatic growth and illusory posttraumatic growth differ in their correlation with well-being. Within the thesis, it was, therefore, primarily suggested that defensiveness could be responsible for illusory posttraumatic growth. The assumption was that high levels of maladaptive defensiveness may be used when distress cannot be endured. Internal and external experiences could then be pushed away. This case could potentially indicate illusory posttraumatic growth. In contrast, people who use low levels of maladaptive defences or high levels of mature defences may be able to endure the distress following a trauma or adversity. Internal and external experiences may be processed and accommodated. This case could potentially indicate real posttraumatic growth. The assumptions about illusions were tested within the thesis. It was investigated which kind of illusions could be adaptive psychological operations and which illusions could be maladaptive psychological operations. The results supported the assumptions within this thesis concerning adaptive versus maladaptive illusions. Within three studies, self-reported posttraumatic growth was significantly correlated with a neurotic defence style. It was concluded that this correlation could indicate that sometimes reports of posttraumatic growth are not real. However, other interpretations were also discussed. Four studies investigated whether real posttraumatic growth and illusory posttraumatic growth differ in their correlation with well-being. Within chapter 5, real posttraumatic growth, indicated by low levels of a neurotic or an immature defence style, was correlated positively with negative change following adversity (non significant). In contrast, illusory posttraumatic growth, indicated by high levels of a neurotic or an immature defence style, was not correlated with negative change following adversity. Although the difference between illusory posttraumatic growth and real posttraumatic growth concerning negative change following adversity had a meaningful effect size, it was not significant. Within chapter 7.3, real posttraumatic growth, indicated by extremely low levels of neurotic defensiveness, was correlated significantly with posttraumatic stress. In contrast, illusory posttraumatic growth, indicated by extremely high levels of neurotic defensiveness, was not correlated with posttraumatic stress. The difference between real posttraumatic growth and illusory posttraumatic growth was significant. Within chapter 8, real posttraumatic growth (high levels of mature defensiveness) was correlated with decreases in hedonic well-being measured by positive and negative affect. In contrast, illusory posttraumatic growth (low levels of mature defensiveness) was correlated with increased levels of hedonic well-being. The difference between real posttraumatic growth and illusory posttraumatic growth was significant. In total, reports of posttraumatic growth may, in fact, sometimes be correlated with defensiveness. However, real posttraumatic growth and illusory posttraumatic growth do only slightly differ concerning their correlation with well-being.